Associação do professorado catharinense: Histories, means of action and composition Associação do professorado catharinense: Histoire, moyens d'action et composition Associação do professorado catharinense: Histórias, meios de ação e composição Associação do professorado catharinense: Historia, medios de acción y composición - Besen D.S.* (2020)
© 2020 Associacao Sul Rio Grandense de Pesquisadores em Historia da Educacao. All rights reserved.This article brings about part of the history of the Associação do Professorado Catharinense, which was founded in the late nineteenth century in Santa Catarina State. Based on studies carried out by Nóvoa (1991, 2006), the organization of professional associations is taken as a stage in the consolidation of the teaching profession. Using historiographic methodology, we selected the following newspapers: A Regeneração, Do Comércio e Conservador, which help in the composition of part of the history of the teaching associations in Santa Catarina State.